Analisis Dana Talangan Pendidikan dalam Perspektif Ekonomi Islam: Studi Kasus Dana Cita Universitas Pelita Bangsa - Hamidah, Siti; Midisen, Kisanda; Ainulyaqin, MH; Mamun, S; Achmad, Yudianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze the costs of education funds at Dana Cita, Pelita Bangsa University. The research method used is descriptive qualitative research. Primary data sources were obtained through interviews with Dana Cita. The results of this research indicate that the application of funding for education funding is using a qardh ijarah agreement. Talang funds are a form of multi-service transaction through the use of an Ijarah contract which is based on an agreement between the bank and customer financing and requires customer financing to pay off debts and obligations. This educational savings fund product is a product that makes things easier for customers, where this product is a solution for customers who have difficulty paying fees for their children to continue their studies or complete their studies.